Construction-related data management - Härkönen, Janne (International journal of management, knowledge and learning, 2023)
The productivity improvement of the construction sector has fallen behind other in dustries. One potential factor is the on-site nature of the work that may not allow for as industrial way of operations as off-site construction. Also, the division into non-optimised chain of domains of architecture, engineering, construction and facil ities management may play a role. The construction objects may not be considered as products that would necessitate careful consideration of the product structure, both commercially and technically to optimise the use of platforms, assemblies, components, and materials while offering what customers desire. Furthermore, the life-cycle of building objects and the varying needs during design, construction and the use-phase are not acknowledged effectively. Addressing the life-cycle of build ing objects necessitates taking command of the relevant data and understanding the bigger picture. Currently the data are managed in an un-organised manner. This study aims to form the pre-requisites for managing construction object-related data. The study is realised as a combination of a literature review and analysing constructors’ offerings, requirements plans, Ministry reports, and building control documentations. A rather detailed example of construction object related data man agement is presented to discuss master data, and business process related data in the context of business processes and enterprise applications, and different Bills of-Materials (BOM) configurations to demonstrate the necessary considerations. The example also acknowledges the product structure, necessary parameters, and stakeholders. New contribution is provided by presenting valuable insights with a broader scope for setting up effective data management in the construction sector.
Keywords: BOM configurations; business data; business processes; construction industry; data management; enterprise applications; gradbeništvo; management; master data; poslovni procesi; product management; product structure; productization; upravljanje izdelkov; upravljanje podatkov